Metagenomic analysis revealed the distribution of antibiotic resistance genes of Awang sheep (Ovis aries) gut microbiota - Zhao, Siyue; Wang, Xinping; Zhu, Heran; Guo, Ge; Mustafa, Ghulam Raza; Mustafa, Ahsan; Chen, Yu; Li, Xiangle; Wang, Ying; Zhao, Bi (Frontiers in Microbiology, 2026)
Antimicrobial resistance (AMR) in livestock is a major contributor to the global AMR crisis, yet little is known about its dynamics in high-altitude pastoral systems. We performed deep metagenomic sequencing of 100 fecal samples from Tibetan Awang sheep reared under grazing (aw_fm) and captive (aw_qs) conditions. Microbiome profiling revealed striking community shifts: grazing sheep were enriched in Bacteroidetes and Firmicutes, whereas captive sheep showed expansion of Proteobacteria, particularly Acinetobacter, suggesting dysbiosis. The resistome comprised 302 unique ARGs, dominated by rpoB2 (43.3%), Bifidobacterium_adolescentis_rpoB (11.2%), and ugd (10.2%). Grazing sheep carried ARGs mainly against rifamycins and peptide antibiotics, reflecting natural selective pressures, while captive sheep exhibited significantly broader resistance, including tetracyclines, macrolides, and fluoroquinolones (p < 0.05). Enrichment of efflux pump genes (MexK, adeJ) in captive sheep highlighted a shift toward multidrug resistance. These findings demonstrate that rearing practices profoundly restructure the gut resistome, underscoring the need for targeted antibiotic stewardship in high-altitude livestock systems.